Studing of sweet corn (Zea mays L. ssp. saccharata Sturt) in the Forest Steppe Zone of Ukraine - А. В. Янчук (Plant Varieties Studying and Protection)
In the Forest Steppe Zone of Ukraine studied 6 sorts and 3 hybrids of sweet com. According with results of research work the author came to the conclusion that sorts and hybrids distinguished some economic- important characteristics.